Impact of stocking density and feeding regimen on broilers: Chicken meat composition, fatty acids, and serum cholesterol levels - Simsek, U. G.; Cerci, I. H.; Dalkilic, B.; Yilmaz, O.; Ciftci, M. (Poultry Science Assoc Inc, 2009)
The purpose of this study was to evaluate the effects of different stocking densities (22.5, 18.75, 15, 11.25, 7.5 broilers/m(2)) in ad libitum (Al) and limited- or pair-feeding (Pf) regimens on meat composition; fatty acid profile of the total carcass, breast meat, and thigh meat; and serum cholesterol level in broiler chickens. (All the Pf groups were provided the same amount of feed per broiler, as determined for the Al-fed group with 22.5 broilers/m(2).) Limited feeding increased the fat ratio of the chicken meat. Lowering the stocking density reduced the fat ratio and increased the protein ratio of the meat in both feeding regimens. The total saturated fatty acid (SFA) ratio was found to be quite high, whereas the total polyunsaturated fatty acid (PUFA) and n-3 fatty acid ratios were found to be low in the limit-fed broilers. Lowering the stocking density had a variable effect on fatty acid composition of the meat; total SFA and monounsaturated fatty acid ratios decreased, whereas total PUFA, n-3, and n-6 ratios increased in the Al groups. Total SFA and monounsaturated fatty acid ratios increased and total PUFA, n-3, and n-6 ratios decreased in the Pf groups. Serum total and high-density lipoprotein cholesterol levels were reduced with lower stocking densities in the Al groups, but only high-density lipoprotein cholesterol was reduced in the Pf groups. Consequently, stocking density and feeding regimen significantly changed the composition, fatty acid profile, and serum cholesterol level of chicken meat.
Keywords: broiler; stocking density; feeding; meat composition; fatty acid; serum cholesterol level